2018
DOI: 10.1186/s13054-018-2030-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of exercise intensity during four early rehabilitation techniques in sedated and ventilated patients in ICU: a randomised cross-over trial

Abstract: BackgroundIn the ICU, out-of-bed rehabilitation is often delayed and in-bed exercises are generally low-intensity. Since the majority of rehabilitation is carried out in bed, it is essential to carry out the exercises that have the highest intensity. The aim of this study was to compare the physiological effects of four common types of bed exercise in intubated, sedated patients confined to bed in the ICU, in order to determine which was the most intensive.MethodsA randomised, single-blind, placebo-controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 43 publications
1
63
0
2
Order By: Relevance
“…The training impact of isolated NMES is inferior to active training with voluntary muscle contractions, [ 13 ] therefore, it is usually proposed to combine NMES with active exercises, [ 14 ] for example, such a combination is used in athletes. [ 15 ] This is not surprising, since NMES provides an additional activation of those muscle fibers that are not involved in the voluntary muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…The training impact of isolated NMES is inferior to active training with voluntary muscle contractions, [ 13 ] therefore, it is usually proposed to combine NMES with active exercises, [ 14 ] for example, such a combination is used in athletes. [ 15 ] This is not surprising, since NMES provides an additional activation of those muscle fibers that are not involved in the voluntary muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…According to these levels of mobility, both passive cycle-ergometry (PCE) and functional electrical stimulation (FES) application provide muscle contraction without increasing cardiovascular work, thus allowing patients with severe ventilatory insufficiency to tolerate this type of peripheral muscle training (6).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, muscle and cardiovascular responses to different forms of bed exercise have never been compared. The most commonly used types of bed exercise are PCE and quadriceps electrical stimulation (6). However, their effects on immune response parameters and nitrosative stress in these patients remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There was a trend toward faster recovery of functional milestones, reduced delirium, and reduced need for rehabilitation posthospital discharge . Medrinal et al explored the impact of 4 different assistive rehabilitation strategies (passive range of motion exercises with therapist, NMES, cycle ergometry, and FES) on cardiorespiratory response to exercise. The study demonstrated that FES cycling was the main intervention, which increased cardiac output and produced sufficient intensity of muscle work; however, a recent study that combined NMES and cycling reported no difference in outcomes in terms of muscle strength and ventilator‐free days or HRQoL at 6 months …”
Section: Introductionmentioning
confidence: 99%